Choosing Appropriate Distribution ‏‎by Minitab’s 17 Software to Analysis System Reliability - Ahmed Abdulrasool Ahmed, Ass. Prof. Dr.; Layla khudheir Jadwa, MSc student (Journal of Engineering, 2015)
This research aims to choose the appropriate  probability ‎ distribution  ‎‏‎ to the reliability‎        analysis‎ for  an   item through ‎ collected data for operating and stoppage  time of  the case  study.